Tracing injected CO2 in the Cranfield enhanced oil recovery field (MS, USA) using He, Ne and Ar isotopes. (November 2015) - Györe, Domokos; Stuart, Finlay M.; Gilfillan, Stuart M.V.; Waldron, Susan
Highlights: Naturally occurring noble gases trace the migration of injected CO2 effectively. The noble gas isotopes identify some loss of injected CO2 from the gas phase. Noble gas isotopes have the potential to quantify the storage of CO2 in CCS sites. Abstract: The He, Ne and Ar isotopic composition of gases collected in 2009 and 2012 from 13 production wells, injection wells and the CO2 supply pipeline at the Cranfield CO2 -enhanced oil recovery field (MS, USA) have been measured in order to determine the extent to which they trace the fate of injected CO2 in the reservoir. In the absence of samples of CO2 pre-injection reservoir gas we use the Ne isotope composition of the production and injection well gases to determine the isotopic composition of the natural gas. The noble gas isotopes display binary mixing trends between the injected CO2 and a CH4 -rich natural gas that is characterised by radiogenic He, Ne and Ar isotope ratios. 3 He/ 4 He and 40 Ar * / 4 He ratios (where 40 Ar * represents the non-atmospheric 40 Ar) display coherent relationships with CO2 concentrations that can be used to trace and quantify the injected CO2 in an engineered site over a sustained period of injection. The presence of a small amount of air-derived Ar, from a non-atmospheric source, in many gas samples rules out using 40 Ar/ 36 Ar to track the injected CO2 . The noble gases identify the loss of a significant proportion of the CO2 from the gas phase sampled by five production wells in 2009. Using 3 He/ 4 He and 40 Ar * / 4 He ratios to reconstruct the major gas composition, it appears that between 22% and 96% of the CO2 has been lost in individual wells. This study demonstrates that the naturally occurring noble gases have the potential to trace the fate and quantify the sequestration of CO2 at injection sites.